Evaluation of a multiparametric immunofluorescence assay for standardization of neuromyelitis optica serology - Granieri, Letizia; Jarius, Sven (PLOS ONE, 2012)
Background Neuromyelitis optica (NMO) is a severely disabling autoimmune disorder of the central nervous system, which predominantly affects the optic nerves and spinal cord. In a majority of cases, NMO is associated with antibodies to aquaporin-4 (AQP4) (termed NMO-IgG). Aims In this study, we evaluated a new multiparametric indirect immunofluorescence (IIF) assay for NMO serology. Methods Sera from 20 patients with NMO, 41 patients with multiple sclerosis (MS), 30 healthy subjects, and a commercial anti-AQP4 IgG antibody were tested in a commercial composite immunofluorescence assay (“Neurology Mosaic 17”; Euroimmun, Germany), consisting of five different diagnostic substrates (HEK cells transfected with AQP4, non-transfected HEK cells, primate cerebellum, cerebrum, and optic nerve tissue sections). Results We identified AQP4 specific and non-specific fluorescence staining patterns and established positivity criteria. Based on these criteria, this kit yielded a high sensitivity (95%) and specificity (100%) for NMO and had a significant positive and negative likelihood ratio (LR+ = ∞, LR− = 0.05). Moreover, a 100% inter- and intra-laboratory reproducibility was found. Conclusions The biochip mosaic assay tested in this study is a powerful tool for NMO serology, fast to perform, highly sensitive and specific for NMO, reproducible, and suitable for inter-laboratory standardization as required for multi-centre clinical trials.
Gesehen am 30.04.2018